Effect of Androgen Deprivation Therapy on Bone Mineral Density in a Prostate Cancer Cohort in New Zealand: A Pilot Study. (6th October 2017) - Wang, Alice; Karunasinghe, Nishi; Plank, Lindsay; Zhu, Shuotun; Osborne, Sue; Bishop, Karen; Brown, Charis; Schwass, Tiffany; Masters, Jonathan; Holmes, Michael; Huang, Roger; Keven, Christine; et al.
Introduction: Reduction in bone mineral density (BMD) is a common side effect of androgen deprivation therapy (ADT). We aimed to examine the cross-sectional and longitudinal variation in BMD and associated bone markers in patients with nonmetastatic prostate cancer (PCa) managed with and without ADT. Methods: Bone mineral density of the total body, lumbar spine, femoral neck, ultradistal forearm, and one-third distal radius was measured in 88 patients with PCa without bone metastases at baseline and at 6 months. Patients were categorized into 4 groups: (1) acute ADT (≤6 months), (2) chronic ADT (>6 months), (3) former ADT, and (4) no ADT (controls). Serum levels of bone metabolism markers, procollagen type I N-terminal propeptide (PINP) and C-terminal cross-linking telopeptide of type I collagen (CTX), were also measured. Results: In the cross-sectional analysis, men receiving chronic ADT had significantly lower total body BMD as compared with former ADT users and men with no ADT. In longitudinal analysis, a significant reduction in ultradistal forearm BMD was observed in both acute and chronic ADT users after 6 months (4.08% and 2.7%, P = .012 and .026, respectively). A significant reduction in total body BMD was observed in acute ADT users (2.99%, P = .032). Former ADT users had a significant increase in both lumbar spine and femoral neck BMD (2.84% and 1.59%, P = .008 and .002, respectively). The changes in BMD were not significantly different between acute and chronic ADT users. In the cross-sectional analysis, higher levels of PINP and CTX were observed in acute and chronic ADT users than former ADT users or PCa controls. In longitudinal analysis, the level of serum PINP and CTX did not change significantly from baseline to 6 months in acute, chronic, and former ADT users, or PCa controls, and the percentage change did not differ among the 4 groups. Conclusions: Men on acute ADT had a similar rate of bone loss to men on chronic ADT. Reversibility in ADT-induced bone loss was observed in those who discontinued ADT. Serum levels of PINP and CTX were higher in acute and chronic ADT users and levels returned to the range of PCa controls when treatment was withdrawn.